Implications of wealth heterogeneity for macroeconomics - Christopher D. Carroll (The Johns Hopkins University, Department of Economics, 2012)
Today's dominant strain of macroeconomic models supposes that aggregate consumption can be understood by assuming the existence of a 'representative agent' whose behavior rationalizes observed outcomes. But representative agent models yield embarrassingly implausible (and empirically inaccurate) descriptions of consumption behavior. When push comes to shove, real-world forecasters (including those at the Fed) properly disregard these implications. As a result, consumption forecasting remains very much a seat-of-the-pants enterprise. I will argue that if the representative agent assumption is replaced with a model that generates wealth heterogeneity that matches the empirical data, the improved model can provide a sensible analysis of economic questions like "What might the consumption response be to economic stimulus payments?"
Keywords: D12; D31; D91; E21; 330; Microfoundations; Wealth Inequality; Marginal Propensity to Consume